TOURISM DEMAND FOR BALI-THE HEGY APPROACH FOR SEASONAL UNIT ROOT TEST - Ida Bagus Made Wiyasha (Journal of Management and Business, 2012)
Tourism plays an important economic role for a destination. This study aims to investigate the behavior of seasonal direct tourist arrivals to Bali. To achieve the aforementioned objective archival data of direct tourist arrivals to Bali from 2001 to 2010 were used. Error Correction Model (ECM) and HEGY approach were applied to analyze the behavior of seasonal tourist arrivals. Wald test was applied in joint test for quarterly parameter. Cusum test were applied to examine the parameter stability for the periods mentioned above. USA, UK, and Japan tourist arrivals were the dependent variables while exchange rates and inflation rates for those mentioned countries were independent variables of the model. The findings of the study are as follows. The ECM results for Japan revealed that in the short run and the long run as well the exchange and inflation rates were negatively related to arrivals. For UK, in the short run exchange rates negatively related to arrivals while inflation rates exhibited positive relation to arrivals. For the US, all exchange rate and inflation rates were positively related to arrivals. Cusum test revealed the following. Japan arrivals exhibited relatively stable parameter for the periods of 2001-2010. UK arrivals showed parameter instability; while US arrivals experienced relatively stable parameter for the periods mentioned earlier. Wald test results showed that all arrivals, USA, UK, and Japan contained a unit root for their quarterly data.